A water-resistant starch-based biodegradable plastic and a preparation method thereof

By using organic acid-epoxy vegetable oil oligomers to conduct esterification reaction with starch, the problem of poor water resistance of starch-based degraded plastics is solved, and high water resistance and low-cost degraded plastic preparation is achieved.

CN116285015BActive Publication Date: 2025-03-18DEZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310344880.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-03-18
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

Starch-based degraded plastics have poor water resistance, which limits their application scope. The macromolecular additives or chemical modification methods used in the prior art have problems such as high cost and the use of toxic chemical agents.

Method used

Organic acid-epoxy vegetable oil oligomers are used as reactive plasticizers for starch to improve the water resistance of starch-based degraded plastics through esterification reactions, and reduce production costs through reasonable proportions and process flow.

Benefits of technology

The excellent water resistance of starch-based degraded plastics is achieved, while simplifying the preparation process, reducing production costs, and avoiding the risk of using toxic chemicals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004159254720000081
    Figure BDA0004159254720000081
  • Figure BDA0004159254720000091
    Figure BDA0004159254720000091
Patent Text Reader

Abstract

The present invention discloses a water-resistant starch-based biodegradable plastic, wherein the raw materials include by weight: 55-70 parts of starch, 25-40 parts of plasticizer, 1-5 parts of reinforcing agent, 0.5-5 parts of cross-linking agent and 0.5-5 parts of compatibilizer; the starch is one or more of corn starch, potato starch or cassava starch; the plasticizer is organic acid-epoxy vegetable oil oligomer; the reinforcing agent is one or more of microcrystalline cellulose, silicon dioxide, chitosan or polyvinyl alcohol; the cross-linking agent is one or both of aminopropyl triethoxysilane or aminopropyl trimethoxysilane; the compatibilizer is stearic acid. The present invention uses low-cost and widely available organic acids and epoxy vegetable oils to synthesize organic acid-epoxy vegetable oil oligomers with cross-linking. Using organic acid-epoxy vegetable oil oligomers as reactive plasticizers for starch, the carboxyl group of the oligomer and the hydroxyl group of starch can undergo esterification reaction, so the synthesized starch-based degradable plastic will have excellent water resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and preparation thereof, and particularly relates to a water-resistant starch-based biodegradable plastic and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Plastic products are widely used in the fields of medicine, agriculture, life, etc., and have become an important material indispensable for economic development. Most traditional plastics (such as polyvinyl chloride, polyethylene, etc.) are made from petroleum, which is difficult to degrade in the natural environment, causing serious pollution to the ecological environment. At the same time, petroleum is a non-renewable resource and is facing depletion. Due to the wide source and renewable nature of biomass resources, bio-based degradable plastics are the current research hotspot in the plastics industry. Statistics show that degradable plastics only account for 1% of the total plastics. Therefore, the research and development of high-performance, low-cost degradable plastics is imminent.

[0004] Starch is a natural polymer compound with abundant resources, wide sources, renewable, good film-forming properties, and can be completely degraded in the natural environment. Starch-based degradable plastics are one of the most important bioplastics. Since starch molecules contain a large number of hydroxyl groups, water-soluble plasticizers are required, resulting in poor water resistance of degradable plastics, which greatly limits its application range.

[0005] In order to overcome the problem of poor water resistance of starch-based degradable plastics, macromolecular substances are usually added or starch is hydrophobically modified. Degradable macromolecular substances such as polylactic acid, polybutylene adipate terephthalate, etc. have higher mechanical properties themselves, which improve the mechanical properties of degradable plastics to a certain extent. However, for degradable plastics based on starch, other macromolecular additions are limited, and the water resistance of degradable plastics is still poor. In the prior art, there is a reactive plasticizer using epoxidized vegetable oil as starch, but starch and epoxidized vegetable oil have poor compatibility, and it is necessary to add compatibilizer and non-degradable polyethylene in addition. Chemical modification can introduce hydrophobic groups, thereby improving the water resistance of degradable plastics, but chemical methods mostly use toxic modifiers (bisphenol A, epichlorohydrin, etc.) and organic solvents (pyridine, dimethylamide, etc.), resulting in excessive production costs. Summary of the invention

[0006] In order to overcome the above problems, the present invention provides a water-resistant starch-based biodegradable plastic and a preparation method thereof.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a water-resistant starch-based biodegradable plastic, the raw materials of which include, by weight: 55-70 parts of starch, 25-40 parts of plasticizer, 1-5 parts of reinforcing agent, 0.5-5 parts of cross-linking agent and 0.5-5 parts of compatibilizer;

[0009] The starch is one or more of corn starch, potato starch or cassava starch; the plasticizer is organic acid-epoxy vegetable oil oligomer; the enhancer is one or more of microcrystalline cellulose, silicon dioxide, chitosan or polyvinyl alcohol; the crosslinker is one or both of aminopropyl triethoxy silane and aminopropyl trimethoxy silane; and the compatibilizer is stearic acid.

[0010] The second aspect of the present invention provides a method for preparing the above-mentioned water-resistant starch-based biodegradable plastic, the method comprising the following steps:

[0011] Starch, plasticizer, reinforcing agent, crosslinking agent and compatibilizer are placed in a reaction container according to weight ratio for mixing and stirring, and then sealed and stored for a period of time, and the sealed and stored mixture is placed in an internal mixer for melt mixing;

[0012] The melt-mixed material is cut into particles by a pelletizer, the particles are dried, and then the dried particles are put into a stainless steel mold and hot-pressed in a hot-pressing molding machine to obtain a water-resistant starch-based biodegradable plastic.

[0013] The beneficial effects of the present invention are:

[0014] The invention adopts low-cost and widely available organic acid and epoxidized vegetable oil to synthesize organic acid-epoxidized vegetable oil oligomers with crosslinking and plasticizing effects. Starch is used as the main raw material to prepare degradable plastics, and organic acid-epoxidized vegetable oil oligomers are used as reactive plasticizers of starch. The carboxyl groups of the oligomers and the hydroxyl groups of starch can undergo esterification reaction, so the synthesized starch-based degradable plastics will have excellent water resistance and simple preparation process. DETAILED DESCRIPTION

[0015] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0016] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the present invention explicitly states otherwise, singular forms are also intended to include plural forms. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0017] A first typical embodiment of the present invention provides a water-resistant starch-based biodegradable plastic, wherein the raw materials include, by weight: 55-70 parts of starch, 25-40 parts of plasticizer, 1-5 parts of reinforcing agent, 0.5-5 parts of cross-linking agent and 0.5-5 parts of compatibilizer;

[0018] The starch is one or more of corn starch, potato starch or cassava starch; the plasticizer is organic acid-epoxy vegetable oil oligomer; the enhancer is one or more of microcrystalline cellulose, silicon dioxide, chitosan or polyvinyl alcohol; the crosslinker is one or both of aminopropyl triethoxy silane and aminopropyl trimethoxy silane; and the compatibilizer is stearic acid.

[0019] In one or more embodiments, the raw materials of the water-resistant starch-based biodegradable plastic include, by weight, 60 parts of starch, 30 parts of plasticizer, 5 parts of reinforcing agent, 2 parts of cross-linking agent and 3 parts of compatibilizer.

[0020] In one or more embodiments, the starch is corn starch; the reinforcing agent is microcrystalline cellulose; and the crosslinking agent is aminopropyltriethoxysilane.

[0021] In one or more embodiments, the organic acid in the organic acid-epoxidized vegetable oil oligomer is citric acid or butanetetracarboxylic acid, preferably citric acid; the epoxidized vegetable oil is epoxidized soybean oil, epoxidized palm oil or epoxidized rice bran oil, preferably epoxidized soybean oil.

[0022] Preferably, the method for preparing the organic acid-epoxidized vegetable oil oligomer comprises the following steps:

[0023] The organic acid and distilled water were mixed in a weight ratio of 1:4, stirred and heated to 75°C to dissolve the organic acid, and then the epoxidized vegetable oil was added. The reaction was continued at 75°C with stirring for 60 minutes. Then, a 50% by volume ethanol aqueous solution was added to the reaction system to terminate the reaction. The reaction solution was placed in a separatory funnel and allowed to stand for 4 hours to separate the layers. The upper oil layer was collected and dried at 60°C for 24 hours to obtain an organic acid-epoxidized vegetable oil oligomer.

[0024] Further preferably, the molar ratio of the carboxyl group of the organic acid to the epoxy group of the epoxidized vegetable oil is 6:1.

[0025] In the present invention, the synthesis temperature of organic acid-epoxidized soybean oil oligomer is reduced by increasing the amount of water used to dissolve the organic acid. At the same time, the molar ratio of the carboxyl group of the organic acid of the present invention to the epoxy group of the epoxidized soybean oil is high, so the synthesized oligomer has a lower crosslinking degree, and the oligomer is more likely to undergo a crosslinking reaction with starch. Furthermore, the present invention purifies the synthesized oligomer, and after the reaction is completed, the unreacted organic acid is removed, thereby avoiding the degradation of starch by the organic acid. Studies have shown that organic acid is acidic, which can cause starch degradation and enhance hydrophilicity.

[0026] Further preferably, the amount of the ethanol aqueous solution added is 5 to 15 times, preferably 10 times, the total volume of the liquid after stirring and reacting for 60 minutes.

[0027] A second typical embodiment of the present invention provides a method for preparing the above-mentioned water-resistant starch-based biodegradable plastic, the method comprising the following steps:

[0028] (1) starch, plasticizer, reinforcing agent, crosslinking agent and compatibilizer are placed in a reaction container according to weight ratio for mixing and stirring, and then sealed and stored for a period of time, and the sealed and stored mixture is placed in an internal mixer for melt mixing;

[0029] (2) The molten mixed material is cut into granules by a pelletizer, the granules are dried, and the dried granules are placed in a stainless steel mold and hot-pressed in a hot-pressing molding machine to obtain a water-resistant starch-based biodegradable plastic.

[0030] In one or more embodiments, the mixing and stirring time in step (1) is 0.5 to 1.5 hours, preferably 1 hour.

[0031] In one or more embodiments, the sealed storage time in step (1) is 12 to 48 hours, preferably 24 hours.

[0032] In one or more embodiments, the temperature of the mixture in step (1) being placed in an internal mixer for melt mixing is 120-180° C., preferably 150° C.; the rotation speed is 80-120 rpm, preferably 100 rpm; and the melt mixing time is 20-40 min, preferably 30 min. Under these conditions, the organic acid-epoxy vegetable oil oligomer and the starch are efficiently plasticized and cross-linked.

[0033] In one or more embodiments, the size of the particles in step (2) is 0.4-0.6 mm, preferably 0.5 mm.

[0034] In one or more embodiments, the drying temperature in step (2) is 70 to 90° C., preferably 80° C.; the drying time is 12 to 48 hours, preferably 24 hours.

[0035] In one or more embodiments, the thickness of the stainless steel mold in step (2) is 0.5 to 2 mm, preferably 1 mm.

[0036] In one or more embodiments, the temperature of the hot pressing molding machine in step (2) is 130-150°C, preferably 140°C; the pressure is 10-30Mpa, preferably 20MPa; and the time of the hot pressing molding is 5-15min, preferably 10min.

[0037] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0038] Example 1

[0039] Preparation of water-resistant starch-based biodegradable plastics

[0040] Mix citric acid and distilled water in a weight ratio of 4:1, stir and heat to 75°C to dissolve the citric acid, add epoxidized soybean oil (the molar ratio of the carboxyl group of citric acid to the epoxy group of epoxidized soybean oil is 6:1), continue stirring and react at 75°C for 60 minutes, finally, add 10 times the volume of the reaction solution of ethanol aqueous solution to terminate the reaction, the volume fraction of ethanol aqueous solution is 50%, place the reaction solution in a separatory funnel and let it stand for 4 hours to separate, collect the upper oil layer, and dry it at 60°C for 24 hours to obtain an organic acid-epoxidized vegetable oil oligomer.

[0041] The following components (kg) were weighed: 60 parts of corn starch, 30 parts of citric acid-epoxidized soybean oil oligomer, 5 parts of microcrystalline cellulose, 2 parts of aminopropyl triethoxysilane and 3 parts of stearic acid, stirred and mixed for 1 hour, and sealed and stored for 24 hours. Then, the mixture was melt-mixed in an internal mixer at 150°C and 100 rpm for 30 minutes to allow the oligomer and starch to be efficiently plasticized and cross-linked.

[0042] The molten mixed material was cut into particles with a size of about 0.5 mm by a pelletizer, the particles were dried in an oven at 80°C for 24 hours, the particles were placed in a stainless steel mold with a thickness of 1 mm, and treated in a hot pressing machine at 20 MPa and 140°C for 10 minutes to obtain a degradable plastic.

[0043] Comparative Example 1 (Changing the type of plasticizer, replacing citric acid-epoxidized soybean oil oligomer with glycerol)

[0044] The following components (kg) were weighed: 60 parts of corn starch, 30 parts of glycerol, 5 parts of microcrystalline cellulose, 2 parts of aminopropyl triethoxysilane and 3 parts of stearic acid, stirred and mixed for 1 hour, and sealed and stored for 24 hours. Then, the mixture was melt-mixed in an internal mixer at 150°C and 100 rpm for 30 minutes to allow the oligomer and starch to be efficiently plasticized and cross-linked.

[0045] The molten mixed material was cut into particles with a size of about 0.5 mm by a pelletizer, the particles were dried in an oven at 80°C for 24 hours, the particles were placed in a stainless steel mold with a thickness of 1 mm, and treated in a hot pressing machine at 20 MPa and 140°C for 10 minutes to obtain a degradable plastic.

[0046] Comparative Example 2 (Changing the Preparation Method of Citric Acid-Epoxidized Soybean Oil Oligomer)

[0047] Mix citric acid and distilled water in a weight ratio of 3:1, stir and heat to 90°C to dissolve the citric acid, add epoxidized soybean oil (the molar ratio of the carboxyl group of citric acid to the epoxy group of epoxidized soybean oil is 3:1), continue stirring and react at 90°C for 45 minutes, finally, add a small amount of glycerol as a diluent, and dry at 60°C for 24 hours to obtain citric acid-epoxidized soybean oil oligomer.

[0048] The following components (kg) were weighed: 60 parts of corn starch, 30 parts of citric acid-epoxidized soybean oil oligomer, 5 parts of microcrystalline cellulose, 2 parts of aminopropyl triethoxysilane and 3 parts of stearic acid, stirred and mixed for 1 hour, and sealed and stored for 24 hours. Then, the mixture was melt-mixed in an internal mixer at 150°C and 100 rpm for 30 minutes to allow the oligomer and starch to be efficiently plasticized and cross-linked.

[0049] The molten mixed material was cut into particles with a size of about 0.5 mm by a pelletizer, the particles were dried in an oven at 80°C for 24 hours, the particles were placed in a stainless steel mold with a thickness of 1 mm, and treated in a hot pressing machine at 20 MPa and 140°C for 10 minutes to obtain a degradable plastic.

[0050] Comparative Example 3 (Changing the Preparation Method of Citric Acid-Epoxidized Soybean Oil Oligomer)

[0051] Mix citric acid and distilled water in a weight ratio of 4:1, stir and heat to 75°C to dissolve the citric acid, add epoxidized soybean oil (the molar ratio of the carboxyl group of citric acid to the epoxy group of epoxidized soybean oil is 6:1), continue stirring and react at 75°C for 60 minutes, and dry at 60°C for 24 hours to obtain an organic acid-epoxidized vegetable oil oligomer.

[0052] The following components (kg) were weighed: 60 parts of corn starch, 30 parts of citric acid-epoxidized soybean oil oligomer, 5 parts of microcrystalline cellulose, 2 parts of aminopropyl triethoxysilane and 3 parts of stearic acid, stirred and mixed for 1 hour, and sealed and stored for 24 hours. Then, the mixture was melt-mixed in an internal mixer at 150°C and 100 rpm for 30 minutes to allow the oligomer and starch to be efficiently plasticized and cross-linked.

[0053] The molten mixed material was cut into particles with a size of about 0.5 mm by a pelletizer, the particles were dried in an oven at 80°C for 24 hours, the particles were placed in a stainless steel mold with a thickness of 1 mm, and treated in a hot pressing machine at 20 MPa and 140°C for 10 minutes to obtain a degradable plastic.

[0054] The degradable plastics prepared in Example 1 and Comparative Examples 1 to 3 were characterized, including their hygroscopicity, water solubility, tensile strength and elongation at break.

[0055] Hygroscopicity test:

[0056] Plastics with a size of 10 mm × 15 mm were dried at 60°C for 24 hours. The samples were then placed in a sealed container (75% RH) filled with a saturated NaCl solution at 25°C until constant weight was achieved. Hygroscopicity is the ratio of the mass increase of the dried sample to the initial sample dry weight, and the results are shown in Table 1.

[0057] Water solubility test:

[0058] The 10 mm x 15 mm bioplastic was dried at 60 °C for 24 h. Then, the sample was immersed in a beaker containing 50 mL of distilled water for 24 h. The insoluble matter was filtered, collected, and dried in an oven until the weight reached a constant. Water solubility is the ratio of the mass of the dissolved substance in water to the initial dry weight, and the results are shown in Table 1.

[0059] Tensile strength and elongation at break test:

[0060] According to ASTM D638, the dumbbell-shaped specimens were tested using a Shimadzu AGS-X tensile testing machine at a tensile rate of 50 mm / min. The results are shown in Table 1.

[0061] Table 1 Performance characteristics of the degradable plastics prepared in Example 1 and Comparative Examples 1 to 3

[0062]

[0063]

Claims

1. A water-resistant starch-based biodegradable plastic, characterized in that: The raw materials include, by weight: 55-70 parts of starch, 25-40 parts of plasticizer, 1-5 parts of reinforcing agent, 0.5-5 parts of cross-linking agent and 0.5-5 parts of compatibilizer; The starch is one or more of corn starch, potato starch or cassava starch; the plasticizer is organic acid-epoxy vegetable oil oligomer; the reinforcing agent is one or more of microcrystalline cellulose, silicon dioxide, chitosan or polyvinyl alcohol; the crosslinking agent is one or both of aminopropyl triethoxysilane or aminopropyl trimethoxysilane; the compatibilizer is stearic acid; The preparation method of the organic acid-epoxidized vegetable oil oligomer comprises the following steps: The organic acid and distilled water were mixed in a weight ratio of 1:4, and the mixture was heated to 75°C with stirring to dissolve the organic acid. Then, the epoxy vegetable oil was added, and the reaction was continued at 75°C with stirring for 60 minutes. Then, a 50% by volume ethanol aqueous solution was added to the reaction system to terminate the reaction. The reaction solution was placed in a separatory funnel and allowed to stand for 4 hours to separate the layers. The upper oil layer was collected and dried at 60°C for 24 hours to obtain an organic acid-epoxy vegetable oil oligomer. The molar ratio of the carboxyl group of the organic acid to the epoxy group of the epoxidized vegetable oil is 6:1, and the organic acid is citric acid or butanetetracarboxylic acid.

2. The water-resistant starch-based biodegradable plastic according to claim 1, characterized in that: The raw materials include, by weight: 60 parts of starch, 30 parts of plasticizer, 5 parts of reinforcing agent, 2 parts of cross-linking agent and 3 parts of compatibilizer.

3. The water-resistant starch-based biodegradable plastic according to claim 1, characterized in that: The starch is corn starch; the enhancer is microcrystalline cellulose; the cross-linking agent is aminopropyl triethoxysilane; The epoxidized vegetable oil is epoxidized soybean oil, epoxidized palm oil or epoxidized rice bran oil.

4. The water-resistant starch-based biodegradable plastic according to claim 1, characterized in that: The organic acid in the organic acid-epoxidized vegetable oil oligomer is citric acid.

5. The water-resistant starch-based biodegradable plastic according to claim 1, characterized in that: The epoxidized vegetable oil is epoxidized soybean oil.

6. The water-resistant starch-based biodegradable plastic according to claim 1, characterized in that: The amount of the ethanol aqueous solution added is 5 to 15 times the total volume of the liquid after stirring and reacting for 60 minutes.

7. The water-resistant starch-based biodegradable plastic according to claim 1, characterized in that: The amount of the ethanol aqueous solution added is 10 times the total volume of the liquid after stirring and reacting for 60 minutes.

8. The method for preparing the water-resistant starch-based biodegradable plastic obtained according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) Starch, plasticizer, reinforcing agent, cross-linking agent and compatibilizer are placed in a reaction container according to weight ratio for mixing and stirring, and then sealed and stored for a period of time, and the sealed and stored mixture is placed in an internal mixer for melt mixing; (2) The molten mixed material is cut into granules by a pelletizer, the granules are dried, and the dried granules are placed in a stainless steel mold and hot-pressed in a hot-pressing molding machine to obtain a water-resistant starch-based biodegradable plastic.

9. The preparation method according to claim 8, characterized in that: The mixing and stirring time in step (1) is 0.5 to 1.5 hours; The sealed storage time in step (1) is 12 to 48 hours.

10. The preparation method according to claim 8, characterized in that: The mixing and stirring time in step (1) is 1 hour.

11. The preparation method according to claim 8, characterized in that: The sealed storage time in step (1) is 24 hours.

12. The preparation method according to claim 8, characterized in that: In the step (1), the temperature of the mixture in the internal mixer for melt mixing is 120-180° C., the rotation speed is 80-120 rpm, and the melt mixing time is 20-40 min.

13. The preparation method according to claim 8, characterized in that: In the step (1), the temperature at which the mixture is put into the internal mixer for melt mixing is 150°C.

14. The preparation method according to claim 8, characterized in that: In the step (1), the mixture is put into an internal mixer for melt mixing at a rotation speed of 100 rpm.

15. The preparation method according to claim 8, characterized in that: In step (1), the mixture is placed in an internal mixer for melt mixing for 30 minutes.

16. The preparation method according to claim 8, characterized in that: The size of the particles in step (2) is 0.4-0.6 mm; The drying temperature in step (2) is 70-90° C. and the drying time is 12-48 hours.

17. The preparation method according to claim 8, characterized in that: The size of the particles in step (2) is 0.5 mm.

18. The preparation method according to claim 8, characterized in that: The drying temperature in step (2) is 80°C.

19. The preparation method according to claim 8, characterized in that: The drying time in step (2) is 24 hours.

20. The preparation method according to claim 8, characterized in that: The thickness of the stainless steel mold in step (2) is 0.5-2 mm; In the step (2), the temperature of the hot pressing molding machine for hot pressing molding is 130-150°C; the pressure is 10-30Mpa; and the time of hot pressing molding is 5-15min.

21. The preparation method according to claim 8, characterized in that: The thickness of the stainless steel mold in step (2) is 1 mm.

22. The preparation method according to claim 8, characterized in that: The temperature of the hot pressing molding machine in the step (2) is 140°C.

23. The preparation method according to claim 8, characterized in that: The pressure of the hot pressing molding machine in the step (2) is 20 MPa.

24. The preparation method according to claim 8, characterized in that: The time for hot pressing molding by the hot pressing molding machine in step (2) is 10 minutes.

Citation Information

Patent Citations

  • Production process of citric acid epoxidized soybean oil oligomer synthesized starch-based bioplastic

    CN117186499A